State Policy and the French Glass Industry, 1640-1789 - Scoville, Warren C. (Quarterly Journal of Economics, 1942)
Development of the different branches of the industry during the period, 430. — I. Classification of establishments, 433. — II. Analysis of charters granted, 435. —III. The control of competition, 437. — Encouragement of new industries, 437. — IV. Later changes in the state's attitude toward monopoly privileges, 439. — V. Regulations not stipulated in charters, 443. — VI. Restrictions on procurement of raw materials, 444. — VII. Maintenance of order between employers and employees, 446. — Special privileges of glass workers, 447. — VIII. Marketing of finished glassware, 449. — IX. Tariffs, excises, etc., 451. — X. Conclusions, 452. —